A DSA-like digital signature protocol. (18th August 2022) - Zahhafi, Leila; Khadir, Omar
Abstract: In this paper we propose a new digital signature protocol inspired by the DSA algorithm. The security and the complexity are analyzed. Our method constitutes an alternative if the classical scheme DSA is broken.